2021
DOI: 10.3389/fpubh.2021.640454
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress in a Gender Perspective: A Survey in a Population of Unemployed Subjects of Southern Italy

Abstract: Stressful life events, are differently handled by women and men. This study evaluates gender differences in perceived stress and health status among a sample of subjects going through a transition period from unemployment to work. This cross-sectional study enrolled 395 participants, 245 men (62%) and 150 (38%) women, between 19 and 67 years, that were going to be hired for a 6-month contract. Before being employed, all participants underwent a mandatory protocol consisting in a general medical check. Stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
9
27
1
5
Order By: Relevance
“…In our study, higher perceived stress was observed among female physical therapy students. Although these gender differences could be related with the effect of the pandemic, they converge with those previously described in the general population samples [ 34 ], university students [ 35 ], and, more specifically, health science students [ 36 ]. Subsequent studies should clarify the relationship between the perceived stress and the COVID-19 pandemic in this population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, higher perceived stress was observed among female physical therapy students. Although these gender differences could be related with the effect of the pandemic, they converge with those previously described in the general population samples [ 34 ], university students [ 35 ], and, more specifically, health science students [ 36 ]. Subsequent studies should clarify the relationship between the perceived stress and the COVID-19 pandemic in this population.…”
Section: Discussionsupporting
confidence: 84%
“…Of those, most are stress-related problems, which are caused by accumulation of damage. Therefore, even if this population is young, it is expected that women will develop stress-related health problems over time [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, precisely owing to these working conditions, healthcare workers are more likely to report a high prevalence of sleep disturbances with consequential psychological disorders affecting daily activities [7]. Therefore, it is possible to observe a reduction in professional performance among medical staff with severe consequences, such as mistakes due to fatigue leading to adverse clinical outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Though it has been demonstrated that the trend of contagion has differently affected the mental health status of HCWs working in areas with dissimilar incidences of COVID-19 cases [ 23 , 24 ], it is also true that regional differences in stress perception and coping strategies also depend on cultural factors, home/work interface, social support, and economic environment [ 25 , 26 ]. In a Chinese study, comparing subjects coming from Hubei and from non-endemic provinces, health workers in the endemic region showed lower anxiety levels about the COVID-19 epidemic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%